‘Rewild My Street’: a model for community-led urban rewilding - Moxon, Sian (Routledge, 2022)
Nature is unintentionally generous to humans, providing valuable ecosystem services, and enhancing our health and wellbeing. Humans are less generous to nature, being responsible for environmental problems, including alarming biodiversity loss. This essay argues for the forging of a more symbiotic relationship between humans and nature, by applying ‘rewilding’ principles to cities to benefit both wildlife and people. Private residential gardens, which make up a quarter of cities, are crucial to this agenda, but are losing greenspace through changes made by residents. To reverse this trend, a new model for implementing policy is needed, as current initiatives prioritise new buildings and public greenspace. Using the London-based ‘Rewild My Street’ campaign as a case study, the chapter shows that solutions can come from generous designers willing to empower communities to effect change themselves. Through open-access resources focused on architectural drawings, the project seeks to inspire residents to transform their homes, gardens and streets for wildlife. The project itself embodies generosity by gifting a sustainable legacy to future generations and other species; sharing architectural knowledge with the public to enable community participation in change; and offering a model for similar projects.